DIGITAL MODULE DESIGN FOR ANIMATION-BASED MICRO MEDIA TRAINING AT SEAMEO SEAMOLEC USING THE LEE & OWENS MODEL: Desain Modul Digital Pelatihan Animation-Based Micro Media Di Seameo Seamolec Menggunakan Model Lee & Owens - Gusnadi, Deviana (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2024)
This research aims to produce a Course Design Specification (CDS) which functions as a reference in the process of developing digital modules for Animation-Based Micro Media training. This research was conducted at SEAMEO SEAMOLEC, South Tanggerang under the auspices of the Training division. The research method used is Research & Development (R&D). The development model used in this research is the Lee and Owens model or by another name Multimedia-based Instructional Design which consists of five stages (Assessment/Analysis, Design, Development, Implementation, and Evaluation). This research focuses on the second stage, namely the Design stage. This stage refers to the results of the analysis that has previously been carried out and concluded. The results of this research consist of five CDS components and their details, namely: (a) Schedule (research schedule); (b) Project team (project team); (c) Media specifications (media specifications); (d) Lesson structure (learning structure); (e) Configuration control and review cycles.